Linux-based remote monitoring system - Wang, Yi. (2010)
An embedded system is a computer system designed to perform one or a few dedicated functions. Embedded system is widely used in industry for various purposes. This project focuses on researching and developing a set of embedded system which is able to provide remote controlling and monitoring functions. Linux is selected to be embedded because its low cost and compatibility to various hybrid board.